2004
DOI: 10.1002/cbf.1069
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence suggesting a role for purine‐catabolizing enzymes in the pathogenesis of cisplatin‐induced nephrotoxicity in rats and effect of erdosteine against this toxicity

Abstract: The aim of this experimental study was to investigate the possible role of adenosine deaminase (AD) and xanthine oxidase (XO) in the pathogenesis of cisplatin-induced nephrotoxicity and the effect of erdosteine in decreasing the toxicity. The intraperitoneal injection of cisplatin (7 mg kg(-1) body weight) induced a significant increase in plasma creatinine level and blood urea nitrogen (BUN), and plasma and damaged renal tissue activities of AD and XO in rats. Co-treatment with erdosteine (10 mg kg(-1)day(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These findings are especially important since XO is included in various pathophysiological processes [38,39] , but not in livers of rats treated with a 7 mg/kg of CP [40] . Interestingly enough the kidney XO was found to be increased by CP application [41] .…”
Section: Resultsmentioning
confidence: 95%
“…These findings are especially important since XO is included in various pathophysiological processes [38,39] , but not in livers of rats treated with a 7 mg/kg of CP [40] . Interestingly enough the kidney XO was found to be increased by CP application [41] .…”
Section: Resultsmentioning
confidence: 95%
“…7 It has been observed that Met I is capable of reacting with reactive oxygen species, nitric oxide, and nitric oxide–derived peroxynitrite and furthermore has both antioxidant and scavenging activities. 18 Erdosteine has been shown to provide protection against cisplatin-induced nephrotoxicity 11,19-21 and cisplatin-induced hepatic oxidant injury 22 when given orally.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that Cis increases free radicals, causes damage to many tissues, and reduces protective activity against the effects of oxidative damage. Therefore, it is hypothesized that Cis-induced nephrotoxicity may result from increased oxidative stress from the increase of free oxygen radicals (9). As a result of various studies conducted in recent years, it has been shown that some side effects of Cis can be reduced without changing the effects of chemotherapy by applying antioxidants obtained by different methods (10,11).…”
Section: Introductionmentioning
confidence: 99%